2019
DOI: 10.21037/tgh.2019.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Venous resection during pancreatectomy for pancreatic cancer: a systematic review

Abstract: Pancreatic cancer is one of the most aggressive and lethal malignancies with a dismal prognosis and survival. The curative effects of venous resection (VR) in pancreatic cancer remain controversial. A systematic literature search was performed in PubMed, Embase and the Cochrane Library. The overall postoperative complications, perioperative mortality, histopathology, and long-term survival were compared between patients undergoing pancreatectomy combined with (VR+ group) or without (VR− group) VR. Forty-one st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…It is unquestionable that venous resection during PD must also aim to obtain negative resection margins, while the reported effects on survival remain controversial [ 61 ]. A meta-analysis showed that pancreatectomy combined with venous resection needed longer operative time and had increased perioperative blood loss compared to the group of pancreatectomy without venous resection [ 62 ]. Patients with venous resection attained reduced R0 rates.…”
Section: Surgerymentioning
confidence: 99%
“…It is unquestionable that venous resection during PD must also aim to obtain negative resection margins, while the reported effects on survival remain controversial [ 61 ]. A meta-analysis showed that pancreatectomy combined with venous resection needed longer operative time and had increased perioperative blood loss compared to the group of pancreatectomy without venous resection [ 62 ]. Patients with venous resection attained reduced R0 rates.…”
Section: Surgerymentioning
confidence: 99%
“…On the other hand, as a strong argument for the topographic hypothesis, complete tumor removal is one of the most important prognostic factors for long-term survival. 36 Interestingly, Mierke et al 37 analyzed recurrence patterns after PDAC resection with VRR. They observed that despite en bloc vascular resection, the true pathologic invasion of SMV/PV constitutes an independent risk factor for OS and DFS, noting a higher incidence of liver metastasis compared with the absence of SMV/PV infiltration.…”
Section: The Role Of Nat Is Emerging But Still Under Explorationmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease, and the five-year survival rate is lower than 8% (1)(2)(3). Although surgery remains the only potential chance for a cure, some patients with localized PDAC are not appropriated for upfront surgery or even unresectable due to the involvement of peripancreatic vessels (3)(4)(5)(6)(7)(8). Regarding patients with peripancreatic arterial involvement, upfront surgery is known to be associated with a low resection rate and a deteriorated long-term survival (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding patients with peripancreatic arterial involvement, upfront surgery is known to be associated with a low resection rate and a deteriorated long-term survival (4,5). In contrast, for patients with isolated peripancreatic venous [portal vein-superior mesenteric vein (PV-SMV)] involvement, long-term survival after extended pancreaticoduodenectomy (PD) with venous resection may be comparable to that achieved by standard PD without venous resection (6)(7)(8). However, the determination of surgical PV-SMV invasion is still based on intraoperative diagnosis (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation